Importance of Social and Cultural Behavior of Korean Managers in the Slovak Republic - in Relation to Sustainable Development of Slovak Tourism - Čuka, Peter (European Journal of Sustainable Development, 2016)
There are significant social and cultural differences between Slovaks and Koreans. Korean managers (of KIA Motors) living in Slovakia have specific requirements, expectations and behavior. In the field of tourism they prefer the classic geographical European destination – especially Germany, Austria, Switzerland and other countries. Their favorite Slovak destinations are High Tatra and Bratislava. The paper is oriented to evaluation of importance of social and cultural behavior of Korean managers and their impact in the sustainability Slovak tourism. The main aim of this paper is to evaluate access of the Koreas managers to Slovak culture, their efforts to learn the Slovak language, understanding the Slovak culture and their loyalty to visit the Slovak destinations as a one of ways to sustainable tourism. Key words:Tourism, Sustainability, CulturalBehavior, SocialBehavior, KoreanManagers